(3ehba GdeedcI GdYQHjI GdSYhOjI ef GdEQgGH (B:s (3OQGSI TQYjI YdejI hKGFbjI (B/s - (3CHG GdNjd, SdjeGf Hf YHO Gddgs 1961- ((3GdQjGV(B:s (3SdjeGf Hf YHO Gddg CHG GdNjd,s, 2009)
(3SGge gPG GdcJGH aj HjGf GdOhQ GdeJejR ddeedcI aj eMGQHI GdEQgGH(B. (3haj OYe GdLghO GdOhdjI, hGdJYGhfjI, hGdJfSjb, hJHGOd GdNHQGJ hOYegG eMdjG hOhdjG dehGLgI GdLQGFe GdeGdjI hGdGbJUGOjI hZjQgG ef GdLQGFe HTcd LeGYj haYGd(B. (3hbO GTJed gPG GdcJGH Ydi KdGKI fbGW gi (B: (3ChdG(B: (3eUGOQ GdOjf GdESdGej, hgj (B: (3GdbQBf GdcQje, hGdSfI GdfHhjI GdeTQaI, hGdELeGY, hGdbjGS(B. (3Ke PcQ GdcGJH CHQR eMGSf GdOjf GdESdGej heRGjGg hgi (B: (3GdCUGdI, GdESdGe Ojf GdaWQI, GdceGd hGdJeGe, GdTehdjI, GdGSJeQGQjI hGdUdGMjI dcd ReGf hecGf hCeI, GdjSQ hQaY GdMQL hGdeTbI, JMbjb GdeUGdM hGdhaGA HGdMGLGJ, GdGLJeGY hGdGJaGb hGdGFJdGa, LdH GdeUGdM hOQA GdeaGSO, GdhSWjI hGdGYJOGd, GdYOd, QYGjI GdeUGdM hGdCeQ HGdEUdGM(B.s
(3jJhaQ abW GdeLdO GdKGfj ef GdcJGHs
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3jJhGaQ HGdecJHI (B: (3eLdO (B1.s
Keywords: (3GdEQgGHs -- (3SjGSI MchejIs -- (3GdSYhOjIs; (3GdEQgGHs -- (3GdSYhOjIs; (3GdESdGe hGdEQgGHs